Actantial Models in the Owl and the Pussy-cat: A Narrative Scheme on Poem - Sarif Syamsu Rizal (LITE: Jurnal Bahasa, Sastra, dan Budaya, 2019)
The study entitled "Actantial Model in The Owl and The Pussy Cat by Edward Lear: A Narrative Scheme on Poem " revealed a narration scheme to find out three models in narration text, namely the function model, action model, and narration model realized in the poem. The approach used to solve the problem is a structuralism approach by using Greimas' Actant theoretical base. The method of data collection in this study is objective literary research. Presentation of data processing is a report using the qualitative description design. The benefits of this study are expected to be one of the developments in literary studies, especially the study of poetic literary works for future students, teachers, researchers and literary critics. The results of this study are the discussion of narration schemes, which consist of the functional model, action model, and narration model of the poem.